GAMBARAN KEKUATAN, DAYA TAHAN OTOT, POWER, KELENTUKAN, KECEPATAN REAKSI, DAN DAYA TAHAN JANTUNG PARU ATLET CABANG OLAHRAGA TENIS MEJA JAWA BARAT PON XVIII/2012 RIAU BERDASARKAN STANDAR KONI PUSAT - Annisa Putri; Mulya Nurmansyah Ardisasmita (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2019)
On PON XVIII/2012 Riau, achievements earned by West Java table tennis athletes were not the best. Those athletes only earned 1 silver medal and 1 bronze medal. One of several factors influencing these athlete’s achievement is physical condition of the athlete. Underwhelming achievements may be caused by discrepancy of athlete’s physical condition with Central KONI standards. This study aimed to describe predominant physical components of West Java table tennis athletes in PON XVIII/2012 Riau according to Central KONI standard. The study was conducted using descriptive study design and cross sectional approach using secondary data that has been measured by Sport Medicine field of KONI West Java. Secondary data consists of predominant physical components in table tennis athletes, which are strength, muscle endurance, power, flexibility, reaction speed, and heart lung strength, that will be compared to Central KONI standard. Based on Central KONI standard, there were predominant physical component of West Java table tennis athletes in PON XVIII/2012 Riau still on deficient and adequate level, which were arm and shoulder muscle strength, leg muscle strength, abdominal muscle endurance, arm muscle power, and heart lung endurance in male athletes; and arm and shoulder strength, abdominal muscle endurance, leg muscle strength, and heart lung endurance in female athletes. There were still predominant physical components of West Java table tennis athletes that have not achieved good, very good or perfect category according to Central KONI standard. Hence, efforts to coach athletes through scalable and well programmed training are needed. In conclusion, an athlete can earn gold medal if predominant physical component capability of said athlete achieved good, very good or perfect category.